Development and delivery of CIS and CSA training materials/curricula in West Africa - Koné, Daouda; Nakayiwa, Florence M.; Zougmoré, Robert B. (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
The Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) Project builds on the initiatives and achievements under the CGIAR Research Program on the Climate Change, Agriculture and Food Security (CCAFS) in Africa. With a focus on climate-smart agriculture (CSA) technologies and on climate information services (CIS), the AICCRA project includes an important capacity development component for the benefit of six (6) countries in Africa. RUFORUM is a global partner to AICCRA to work in West Africa and the East and Sothern Africa but also to work at the continental level. AICCRA will collaborate with the African Regional Universities Forum for Capacity Building in Agriculture (RUFORUM) to develop curricula and training materials that will make accessible to other SSA countries, the knowledge on CSA and climate agro- advisory services generated in the six intervention countries. In partnership with other players, RUFORUM envisages to mobilise universities to contribute towards the Project Development Objective: To strengthen the capacity of targeted CCAFS partners and stakeholders, and to enhance access to climate information services and validated climate-smart agriculture technologies in IDA eligible countries in Africa.